(untitled) (Research, Society and Development, 2024)
Temporomandibular dysfunction (TMD) and headaches are challenging health issues and represent the second cause of chronic facial pain in the world population. They present convergence in treatment, with botulinum toxin being a second-line resource for refractory cases. With the aim of mapping information on the topic, this scoping review was carried out using the elements of the PCC acronym to formulate the question: “What has been produced in the literature about the use of botulinum toxin A in patients with TMD and headache refractory to initial therapy?”. The population was defined by patients with TMD and headaches; in the concept, botulinum toxin A was used in the context of patients refractory to treatment. The databases used were: Pubmed, LILACS, Cochrane and gray literature. Two researchers, blindly, used the Rayyan reference manager to judge the inclusion and exclusion criteria of the articles. Varied study designs were included, without restrictions on language or year of publication. Disagreements were resolved by a third evaluator. The articles selected for reading went on to data extraction. The studies did not present uniformity in their designs and there was no consensus on the results. Pain improvement was observed in more than 80% of the studies, while the increase in mouth opening was the data that presented the most controversial results. Quality of life analysis remained an unexplored gap.